Attitudes Toward Long-Term Medication Use—A Comparison Between Concerned Populations and a Sample From the German General Population: An Example of Real World Evidence. Issue 4 (July 2019) - Engelke, Christina; Cordes, Joachim; Kahl, Kai G.; Schmidt-Kraepelin, Christian
Abstract: Purpose/Background: The present study was conducted to investigate the difference in attitudes toward psychiatric drugs, long-term medication, and depot formulations between psychiatric patients and patient-related groups and the German general public. Methods/Procedures: Different groups (n = 50 patients, n = 34 relatives of patients, n = 42 psychiatrists, n = 70 medical students, and n = 58 psychiatric nursing professionals) were surveyed using a questionnaire to investigate their attitude toward depot medication and compared with matched participants from the German general public. Findings/Results: Patients did not differ from their matched controls regarding their attitude toward potential reasons to reject a depot, whereas psychiatrists ( P = 0.002) and nursing staff ( P = 0.003) were more concerned about patients fearing an injection than their matched controls. Implications/Conclusions: Psychiatrists and psychiatric nurses were significantly more concerned about giving an (intragluteal) injection because of concerns about patients' fears of this administration method than their matched controls. In contrast, patients' concerns about receiving an injection did not differ from their matched controls. Furthermore, we found that psychiatrists tended to believe that giving an injection might be time-consuming than giving oral medication. These results may emphasize the fact that the low rate of depot medication use is derived from subjective reservations of medical staff rather than actual negative attitudes or fears of patients.